2020
DOI: 10.1371/journal.pone.0235959
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the key factors that influence the girls to enter into child marriage: A meta-synthesis of qualitative evidence

Abstract: In this study, we synthesized findings from qualitative studies to identify the key factors that influence child marriage. We used a meta-ethnographic approach coupled with thematic synthesis. We searched literature from nine databases, which were in English language, covering areas in public health, psychology, and social science between 2008 and 2018. Twelve studies were included in the synthesis. We identified six main themes: human insecurity and conflict; legal issues; family values and circumstances; rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 37 publications
4
52
0
1
Order By: Relevance
“…Conversely, looking at a sample of 60 countries, Collin and Talbot (2017) found that – despite increases in legal provisions – most countries do not enforce the proposed laws, and enforcement is not getting better over time. Another recent synthesis from a meta-ethnographic approach reached the similar conclusion that in spite of global progress scaling up legislation against child marriage, the legal framework in many settings is insufficiently enforced ( Kohno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, looking at a sample of 60 countries, Collin and Talbot (2017) found that – despite increases in legal provisions – most countries do not enforce the proposed laws, and enforcement is not getting better over time. Another recent synthesis from a meta-ethnographic approach reached the similar conclusion that in spite of global progress scaling up legislation against child marriage, the legal framework in many settings is insufficiently enforced ( Kohno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…UNICEF reports a reduction in the global prevalence of child marriage in the last decade, largely driven by prevention and care interventions in South Asia. However, 12 million girls per year still get married before the age of 18 ( Kohno et al, 2020 ; UNICEF, 2019 ). The highest levels of child marriage are found in Sub-Saharan Africa (38 percent), with Niger reporting a prevalence as high as 76 percent, followed by South Asia (30 percent) and Latin America (25 percent) ( UNICEF, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large health and financial burden of child marriage and early maternal age at first birth. Girl-child marriage interrupts the development and wellbeing of women by disrupting or often halting education and future employment opportunities, interpersonal violence, and increased risk of early pregnancy [ 5 , 6 , 7 ]. Girl-child marriage was found to be a potential reason for early pregnancy, low birth weight of the child, higher child morbidity and mortality [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The socioeconomic status of women and their household were found to be associated with child marriage in Bangladesh [ 6 , 26 , 27 , 28 ]. For example, child marriage was more prevalent in rural areas compared to urban [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Di Indonesia, perkawinan anak juga diperparah oleh ada anggapan umum bahwa anak perempuan tidak perlu melanjutkan pendidikan tinggi karena pada akhirnya mereka akan menjadi ibu rumah tangga. Angka pernikahan anak lebih rendah untuk anak perempuan yang yang telah menyelesaikan pendidikan menengah atas atau lebih tinggi yang dibuktikan dalam sebuah studi tahun 2020 menunjukkan bahwa menyelesaikan sekolah menengah dapat melindungi anak perempuan untuk menikah sejak dini di Indonesia 11 .…”
Section: Taraf Pendidikanunclassified